2018
DOI: 10.1063/1.5026291
|View full text |Cite
|
Sign up to set email alerts
|

Origin and roles of oxygen impurities in hexagonal boron nitride epilayers

Abstract: Photoluminescence emission spectroscopy and electrical transport measurements have been employed to study the origin and roles of oxygen impurities in hexagonal boron nitride (h-BN) epilayers grown on sapphire substrates. The temperature dependence of the electrical resistivity revealed the presence of a previously unnoticed impurity level of about 0.6 eV in h-BN epilayers grown at high temperatures. The results suggested that in addition to the common nitrogen vacancy (V N) shallow donors in h-BN, oxygen impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…S4) are observed from the post-annealed h-BN film while no exciton-related peak is observed from the as-grown h-BN film that is attributed to the disordered h-BN structure quenching the excitonic PL 5153 . The transition peaks related to a donor-acceptor pair (DAP) transition at 303.4 nm together with its replicas at 317 and 332.8 nm 54 , as well as the emission peaks at 226 and 232 nm originating from the excitons localized at certain structural defects 55 appear after the post-annealing. Although near band-edge phonon replicas of indirect exciton resulting in emission at wavelength shorter than 215 nm is not observed, we believe that remarkable enhanced PL enabled by improved crystallinity after the post-annealing can provide a great opportunity for use of the large-area, multi-wafer scale h-BN film grown by MOCVD as a highly efficient active material in optoelectronic applications.…”
Section: Resultsmentioning
confidence: 99%
“…S4) are observed from the post-annealed h-BN film while no exciton-related peak is observed from the as-grown h-BN film that is attributed to the disordered h-BN structure quenching the excitonic PL 5153 . The transition peaks related to a donor-acceptor pair (DAP) transition at 303.4 nm together with its replicas at 317 and 332.8 nm 54 , as well as the emission peaks at 226 and 232 nm originating from the excitons localized at certain structural defects 55 appear after the post-annealing. Although near band-edge phonon replicas of indirect exciton resulting in emission at wavelength shorter than 215 nm is not observed, we believe that remarkable enhanced PL enabled by improved crystallinity after the post-annealing can provide a great opportunity for use of the large-area, multi-wafer scale h-BN film grown by MOCVD as a highly efficient active material in optoelectronic applications.…”
Section: Resultsmentioning
confidence: 99%
“…The luminescence properties of hBN have been studied mainly in recent years. [ 7,9–15 ] Museur et al reported three photoluminescence (PL) bands at the energies of 5.3, 3.75, and 3.1 eV for pyrolytic hBN (pBN) samples. [ 9 ] pBN samples are high‐purity samples, free of carbon and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the impure sample, which contains a subtle amount of carbon and oxygen, 5 shows additional luminescent structures in the region between 300 and 400 nm (the origin of which is still controversial. 5,[8][9][10][11][12][13] ) Moreover, owing to the relaxation process of excited carriers through excitons to the impurity bands, the intensity of the exciton luminescence for the impure sample is lower than that for the pure sample. 14 In fact, such an impurity-incorporated domain is often contained in HPHT single crystals.…”
Section: Introductionmentioning
confidence: 99%